Pengembangan Instrumen Tes Kimia Framework PISA untuk Mengukur Kemampuan Literasi Sains Siswa Madrasah Aliyah - Winda Ariani; Nahadi; Heli Siti Halimatul Munawaroh (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to produce a valid and reliable PISA-based chemistry test instrument on the acid–base concept to measure Madrasah Aliyah students’ scientific literacy. The test instrument was developed using the ADDIE model (analyze, design, develop, implement, and evaluate). A total of 25 multiple-choice questions were tested on 60 Grade XII students majoring in natural sciences at Madrasah Aliyah in Subang. From the Rasch analysis, a Cronbach's alpha value of 0.71 indicates that the reliability of the test instrument is acceptable. In addition, the person reliability value of 0.67 indicates that the respondents' answers were quite consistent, and the item reliability value of 0.83 indicates that the reliability of the questions was good. All questions were declared valid because they met the outfit MNSQ, outfit ZSTD, and Pt-Measure Correlation criteria. The level of difficulty of the items was distributed into five very easy items, seven easy items, nine difficult items, and four very difficult items. The discriminating power of the items was classified into 24 items in the good category and one item in the sufficient category. In addition, 21 items had well-functioning distractors, while four items had distractors that did not function well.